Critical discourse analysis of climate justice at the COP27 - Hijrah, Nur; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This study examines how climate justice was discursively constructed in official statements delivered at the 2022 United Nations Climate Change Conference in Egypt. It aims to identify and compare the discursive strategies used by a representative developed actor, the European Union, and a developing actor, Pakistan speaking for the Group of 77 and China, and to analyze how linguistic features frame Loss and Damage as either historical responsibility and compensation or as a technical capacity issue. Employing a descriptive qualitative design grounded in Norman Fairclough's three-dimensional model of Critical Discourse Analysis, the research analyzes textual data from the two actors' public statements using a systematic procedure that includes keyword identification, grammatical and lexical analysis, and contextual interpretation. The findings reveal a clear discursive divergence: Pakistan constructs climate justice as a demand for reparative justice based on historical responsibility. In contrast, the European Union frames the issue as a capacity gap, privileging procedural solutions, and funding arrangements that depoliticize liability. The conference outcome to establish a Loss and Damage fund constituted a symbolic success for justice claims but adopted flexible, non-binding arrangements that preserve developed actors' influence.